PENGARUH OPERATING PROFIT MARGIN, RETURN ON ASSET, LEVERAGE, DAN SIZE TERHADAP NILAI PERUSAHAAN - Heri Winarto, 11.42.02.0045 (Students Journal of Economic and Management, 2013)
This study examined the effect of disclosure of Operating Profit Margin (OPM), Return On Asset (ROA), Leverage, and Size To Firm Value. The sample in this study is a manufacturing company listed in Indonesian Stock Exchange (IDX) in span of years 2008â2011. Study sample is as much as 78 companies with 312 observations. Analysis of data using multiple regression analysis to all hyphotesis. The results showed that the Operating Profit Margin (OPM), Return on Asset (ROA), Leverage ratio, and Size have a significant effect to firm value. With Goodness of Fit Test showed that 40,8% Operating Profit Margin (OPM), Return on Asset (ROA), Leverage raio, and given effect to firm value, while the rest equal to 59,2% influenced by others variable which do not check. Keyword:Firm Value, Operating Profit Margin (OPM), Return on Asset (ROA), Leverage Ratio (LR), Size